Detection of glaucoma using operator-dependent versus operator-independent classification in the Heidelberg retinal tomograph-III. Issue 11 (26th July 2006) - Harizman, N; Zelefsky, J R; Ilitchev, E; Tello, C; Ritch, R; Liebmann, J M
Abstract : Objective: To compare the abilities of a new Glaucoma Probability Scoring (GPS) system and Moorfields regression analysis (MRA) to differentiate between glaucomatous and normal eyes using Heidelberg retinal tomograph (HRT)-III software and race-specific databases. Methods: In this prospective study, one eye (refractive error ⩽5 D) each of consecutive normal patients and those with glaucoma was enrolled. All patients underwent a full eye examination, standard achromatic perimetry (Swedish Interactive Threshold Algorithm-standard automated perimetry (SITA-SAP), program 24-2) and confocal scanning laser ophthalmoscopy (HRT-II) within 1 month. Normal patients had two normal visual fields in both eyes (pattern standard deviation (PSD) >5% and Glaucoma Hemifield Test within 97% normal limits) and a normal clinical examination. Glaucoma was defined on the basis of SITA-SAP visual field loss (PSD<5% or Glaucoma Hemifield Test outside normal limits) on two consecutive visual fields. HRT-II examinations were exported to the HRT-III software (V.3.0), which uses an enlarged race-specific database, consisting of 733 eyes of white people and 215 eyes of black people. Race-adjusted MRA for the most abnormal sector (operator-dependent contour line placement) was compared with the global race-adjusted GPS (operator independent). MRA sectors outside the 99.9% confidence interval limits (outside normal limits) and GPS ⩾0.64 were considered abnormal. Results: 136 normal patients (72 black and 64 white patients) and 84 patients with glaucoma (52 black and 32 white patients) were enrolled (mean age 50.4 (SD 14.4) years). The average visual field mean deviation was −0.4 (SD 1.1) db for the normal group and −7.3 (SD 6.7) db for the glaucoma group (p<0.001). Mean GPS values were 0.21 (SD 0.23) and 0.73 (SD 0.27) for normal and glaucomatous eyes, respectively (p<0.001). Sensitivity and specificity values were 77.1% and 90.3% for GPS, and 71.4% and 91.9% for MRA, respectively. Conclusions: In this cohort, GPS software sensitivity and specificity values are similar to those of MRA, which requires placement of an operator-dependent contour line. The development of software to detect glaucoma without a contour line is critical to improving the potential use of HRT as a tool for glaucoma detection and screening.